2013
DOI: 10.1179/1351000213y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/apyrimidinic endonuclease 1, the sensitive marker for DNA deterioration in dextran sulfate sodium-induced acute colitis

Abstract: Mutations in mismatch repair (MMR) genes are commonly associated with the development of colorectal cancer. Additionally, base excision repair, which involves apurinic/apyrimidinic endonuclease 1 (APE1), recognizes and eliminates oxidative DNA damage. Here, we investigated the possible roles of APE1 in dextran sulfate sodium (DSS)-induced acute colitis using the young rat model. Four-week-old Sprague-Dawley rats were administered 2% DSS in drinking water for 1 week. MMR and APE1 expression levels were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Our study provides novel findings on the presence of APE1/Ref-1 in enteric neurons and increased level of APE1/Ref-1 in both the mucosa and myenteric ganglia in the colons from Winnie mice. These results are consistent with findings in the colon tissues removed from IBD patients with active inflammation (Hofseth et al 2003) and in the colonic epithelium of an animal model of DSS-induced colitis (Chang et al 2013). Inflammation caused by pathogenic bacteria, ionising radiation, ROS and toxic agents transiently increase intracellular APE1/Ref-1 in gastric epithelial cells and sensory neurons (O'Hara et al 2006;Vasko et al 2011).…”
Section: Apx3330 Treatment Alleviated Enteric Neuropathy In Winnie Micesupporting
confidence: 88%
See 2 more Smart Citations
“…Our study provides novel findings on the presence of APE1/Ref-1 in enteric neurons and increased level of APE1/Ref-1 in both the mucosa and myenteric ganglia in the colons from Winnie mice. These results are consistent with findings in the colon tissues removed from IBD patients with active inflammation (Hofseth et al 2003) and in the colonic epithelium of an animal model of DSS-induced colitis (Chang et al 2013). Inflammation caused by pathogenic bacteria, ionising radiation, ROS and toxic agents transiently increase intracellular APE1/Ref-1 in gastric epithelial cells and sensory neurons (O'Hara et al 2006;Vasko et al 2011).…”
Section: Apx3330 Treatment Alleviated Enteric Neuropathy In Winnie Micesupporting
confidence: 88%
“…In our study, oxidative stress in myenteric neurons and surrounding cells was shown by the increased mitochondrial superoxide production in Winnie mice. Myenteric neurons in Winnie mice exhibit increased mitochondrial superoxide and oxidative stress-induced DNA damage, as seen in multiple studies that describe increase in oxidative DNA damage in the colonic mucosa of IBD patients (D'Incà et al 2006;Dincer et al 2007;Lih-Brody et al 1996) and chemically-induced colitis (Chang et al 2013). Our results demonstrate that APX3330 reduced oxidative stress via its redox inhibition of APE1/Ref-1 and oxidative DNA damage in chronic colitis.…”
Section: Apx3330 Treatment Alleviated Enteric Neuropathy In Winnie Micesupporting
confidence: 78%
See 1 more Smart Citation
“…Several preclinical investigations demonstrate that APE1 is an effective target in treating IBD [32,67]. For instance, Chang et al induced IBD in rats with dextran sulfate sodium (DSS) administration, which initially induces colonic injury, and then further causes chronic colitis over the time.…”
Section: Ape1 In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…For instance, Chang et al induced IBD in rats with dextran sulfate sodium (DSS) administration, which initially induces colonic injury, and then further causes chronic colitis over the time. They revealed that APE1 and MSH2 (mismatch repair gene) levels were significantly increased in a timedependent manner with DSS-treatment [68]. In addition, DNA damage marker 8-hydroxy-deoxyguanosine (8-OHdG) was increased in the colonic mucosa, whereas APE1 levels in the surface epithelium increased at an earlier timepoint, highlighting the fact that APE1 is a sensitive target for determining exacerbation of DNA damage in DSS-induced colitis [68].…”
Section: Ape1 In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%